Cross-cultural adaptation of the Patient-Doctor Relationship Questionnaire (PDRQ-9) in Brazil - Lucas Wollmann; Lisiane Hauser; Sotero Serrate Mengue; Milena Rodrigues Agostinho; Rudi Roman; Christina M Van Der Feltz-Cornelis; Erno Harzheim (Revista de Saúde Pública, 2018)
ABSTRACT OBJECTIVE To describe the process of cross-cultural adaptation of the Patient-Doctor Relationship Questionnaire (PDRQ-9), as well as compare the agreement between two different types of application. METHODS This is a cross-sectional study with 133 adult users of a Primary Health Service in Porto Alegre, State of Rio Grande do Sul, Brazil. The PDRQ-9 was answered by the participants as a self-administered questionnaire and in an interview. The instrument was also validated by interview, using data from 628 participants of the Mais Médicos Program Evaluation Research, which is a cross-sectional study with a systematic sample of Primary Care Services in all regions of Brazil. We evaluated the semantic, conceptual, and item equivalence, as well as factor analysis and reliability. RESULTS All items presented factor loading > 0.5 in the different methods of application and populations in the factor analysis. We found Cronbach’s alpha of 0.94 in the self-administered method. We found Cronbach’s alpha of 0.95 and 0.94 in the two different samples in the interview application. The use of PDRQ-9 with an interview or self-administered was considered equivalent. CONCLUSIONS The cross-cultural adaptation of the PDRQ-9 in Brazil replicated the factorial structure found in the original study, with high internal consistency. The instrument can be used as a new dimension in the evaluation of the quality of health care in clinical research, in the evaluation of services and public health, in health management, and in professional training. Further studies can evaluate other properties of the instrument, as well as its behavior in different populations and contexts.